Guillain–Barré syndrome: pathophysiology, etiology, causes, and treatment - Rahman, Rahmathulla S.; Bauthman, Moayyad S.; Alanazi, Amer M.; Alsillah, Naif N.; Alanazi, Ziyad M.; Almuhaysin, Mahdi I.; Almutairi, Ruyuf K.; Binobaid, Kadhem S.; Alharthi, Yousef H.; Bawareth, Rime M.; Alrawili, Omar N. (International Journal Of Community Medicine And Public Health, 2021)
Guillain–Barré syndrome (GBS) is a polyradiculoneuropathy autoimmune disease that is characterized by significant inflammation that affects the peripheral nervous system in a rapidly progressive pattern that is mainly clinically presented by muscle weakness. The present literature review aims to broadly discuss GBS: etiology, pathophysiology and management in order to gain an understading of the existing studies that are relevant to this literature review. Among the reported antibodies, anti-GM1 and anti-GQ1B have been reported to be responsible for attacking and damaging either the neuromuscular junctions or peripheral nerves. Moreover, it has been found that the anti-GD1a antibodies in patients bind to the neuromuscular junction and also bind to the nodes of Ranvier of the peripheral nerves and the paranodal myelin of the affected nerves. Reports have shown that this disease is identified as special forms of neuropathies that develop in immune-mediated, post-infection sequelae. Furthermore, in another study it was reported that Molecular mimicry has been previously reported to significantly correlate with the development of the disease as it was investigated in animal models. In addition, Campylobacter jejuni, a pathogen that causes gastrointestinal infections has been previously reported to predispose to the development of GBS in humans. However, scientists have found that plasma exchange and intravenous immunoglobulins (IVIG) remain the most significant and efficacious factors in managing the disease. Nevertheless, recent trials have investigated other approaches that are less efficacious and can lead to serious adverse events and complications.